2019
DOI: 10.1136/esmoopen-2019-000487
|View full text |Cite
|
Sign up to set email alerts
|

Female oncologists in the Middle East and North Africa: progress towards gender equality

Abstract: BackgroundFemale doctors are increasingly choosing oncology as a career while they are still under-represented in leadership positions globally. The European Society of Medical Oncology has recently surveyed its members regarding gender equality in the work place. Limited data are available from the Middle East. The aim of our study was to survey female oncologists practicing in the Middle East to identify common challenges and suggest areas for improvement.MethodsA cross-sectional survey was distributed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…These are all widely reclaimed means of addressing gender equality across geographical regions. 2 , 10 , 16 In a study by Riaz et al., while women in the United States are clearly underrepresented in senior academic hematology and oncology positions (22% of full professors, 36% of associate professors, and 45% of assistant professors), after adjusting for clinical experience, academic productivity, and workplace ranking, the odds of obtaining professorship were not significantly different for female and male physicians. 30 This supports the theory that for women to reach equal leadership representation, differences in length of clinical experience need to be addressed, and publication profiles and workplace visibility must be increased.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These are all widely reclaimed means of addressing gender equality across geographical regions. 2 , 10 , 16 In a study by Riaz et al., while women in the United States are clearly underrepresented in senior academic hematology and oncology positions (22% of full professors, 36% of associate professors, and 45% of assistant professors), after adjusting for clinical experience, academic productivity, and workplace ranking, the odds of obtaining professorship were not significantly different for female and male physicians. 30 This supports the theory that for women to reach equal leadership representation, differences in length of clinical experience need to be addressed, and publication profiles and workplace visibility must be increased.…”
Section: Discussionmentioning
confidence: 94%
“… 17 Other factors such as difficulties in attending international conferences or training programs, and lower salaries were more prominently cited in surveys of female oncologists in the Middle East, North Africa, and India. 10 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major sources of ionizing radiation includes radioactive material from nuclear waste and medical examinations (for example, computerized tomography and x-rays), and there is an increased probability of exposure to ionizing radiation. Additionally, as society and societal roles have developed, there are now more women in the workforce which may result in additional work-related stress and thus changes to hormone levels (20).…”
Section: Introductionmentioning
confidence: 99%
“…In volunteer home countries, pursuing leadership positions can be challenging for women. In a study of female oncologists in the Middle East, mothers were discouraged from pursuing leadership, even though they felt capable [17]. In an expanded study of female healthcare workers in the U.S., Haiti, Tanzania, and India, 53% reported that gender discrimination prevented promotions [18].…”
Section: An All-female Professional Environment Helped To Develop Femmentioning
confidence: 99%